Maintenance of air worthiness of aircrafts - Горячев, В. А. (Proceedings of National Aviation University (archive), 2000)
Described are modem conditions of operation of Russian civil aviation, state of aircraft stock, the main principles of maintaining air worthiness of airplanes and helicopters. Considered is a stage by stage prolongation of the service life of each specimen of aircraft with certification being obligatory